Microbial assisted alleviation of nickel toxicity in plants: A review - Xinyu Mao; Bilal Ahmad; Sabir Hussain; Farrukh Azeem; Muhammad Waseem; Yousef Alhaj Hamoud; Hiba Shaghaleh; Amany H.A. Abeed; Muhammad Rizwan; Jean Wan Hong Yong (Ecotoxicology and Environmental Safety)
Nickel (Ni) is required in trace amounts (less than 500 µg kg−1) in plants to regulate metabolic processes, the immune system, and to act as an enzymatic catalytic cofactor. Conversely, when nickel is present in high concentration, it is considered as a toxic substance. Excessive human nickel exposure occurs through ingestion, inhalation, and skin contact, ultimately leading to respiratory, cardiovascular, and chronic kidney diseases. Due to anthropogenic activities, the nickel concentrations in various environmental scenarios have progressively risen to levels as high as 26,000 ppm in soil and 0.2 mg L−1 in water; surpassing the established safety threshold limits of 100 ppm for soil and 0.005 ppm for surface water. Nickel is required by various plant species for facilitating biological processes; in the range of 0.01–5 µg g−1 (dry weight). When present in excess, nickel toxicity in plants (10–1000 mg kg−1 dry weight mass) causes many disrupted metabolic processes; leading to lower growth, altered development, hindered seed germination, chlorosis, and necrosis. To tackle any metal-linked pollution issues, various remediation approaches are employed to remove heavy metals (especially nickel) and metalloids including physicochemical, and biological methods. Based on literature, the physicochemical methods are not commonly used due to their costly nature and the potential for producing secondary pollutants. Interestingly, bioremediation is considered by many practitioners as an easy-to-handle, efficient, and cost-effective approach, encompassing techniques such as phytoremediation, bioleaching, bioreactors, green landforming, and bio-augmentation. Operationally, phytoremediation is widely utilized for cleaning up contaminated sites. To support the phytoremediative processes, numerous nickel hyperaccumulating plants have been identified; these species can absorb from their surroundings and store high concentrations of nickel (through various mechanisms) in their biomass, thereby helping to detoxify nickel-contaminated soils via phytoextraction. The microbe-assisted phytoremediation further optimizes the nickel detoxification processes by fostering beneficial interactions between microbes and the nickel-hyperaccumulators; promoting enhanced metal uptake, transformation, and sequestration. Microbe-assisted phytoremediation can be categorized into four subtypes: bacterial-assisted phytoremediation, cyanoremediation, mycorrhizal-assisted remediation, and rhizoremediation. These diverse approaches are likely to offer more effective and sustainable remediative strategy to ecologically restore the nickel-contaminated environments.